Competitor analysis and competitive strategies - Jasmina Ognjanović (Mенаџмент у хотелијерству и туризму, 2015)
Competitors are an integral part of the microenvironment whose business heavily affects the activities of a particular organization, its growth, profitability, market share. The organization needs to keep up with the events in the competitive environment, anticipate the actions of competitors and take advantage of their weaknesses. For these purposes, the Porter's framework of "five factors", including the rivalry among existing organizations, the risk of potential newcomers, customer bargaining power, bargaining power of suppliers and substitutes, is used. In order to enable organizations to successfully defend their market position and increase their market share specific competitive strategies have been developed including: the market leader strategy, market-challenger strategy, market-follower strategy and market-nicher strategy.